2013
DOI: 10.2147/nss.s42641
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific pain is a marker for hypovitaminosis D in patients undergoing evaluation for sleep disorders: a pilot study

Abstract: BackgroundThe purpose of this cross-sectional study was to test the hypothesis that serum vitamin D levels are abnormally low in sleep clinic patients admitting to chronic nonspecific musculoskeletal pain and to assess the associated risk factors. A secondary purpose was to identify a clinical biomarker for vitamin D deficiency.MethodsWe enrolled 153 consecutive patients who admitted to the presence of chronic nonspecific musculoskeletal pain during a comprehensive sleep evaluation at a specialist sleep medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A study evaluating the effects of cholecalciferol supplementation (1200 IU/ day to individuals with serum 25OHD between 20 and 29 ng/mL and 50,000 IU/weekly to those with serum 25OHD <20 ng/mL) in veterans with multiple areas of chronic pain found a decrease in self-reported pain in both supplemented groups, as well as an improvement in sleep pattern, with decreased sleep latency and increased sleep duration (Huang et al 2013). In another study, patients with nonspecific chronic pain selected from a sleep clinic showed serum 25OHD levels <20 ng/mL (McCarty et al 2013). The risk factors for the decrease of vitamin D status in this study were ethnicity, obesity and age.…”
Section: Future Perspectives: Vitamin D Sleep and Painmentioning
confidence: 93%
“…A study evaluating the effects of cholecalciferol supplementation (1200 IU/ day to individuals with serum 25OHD between 20 and 29 ng/mL and 50,000 IU/weekly to those with serum 25OHD <20 ng/mL) in veterans with multiple areas of chronic pain found a decrease in self-reported pain in both supplemented groups, as well as an improvement in sleep pattern, with decreased sleep latency and increased sleep duration (Huang et al 2013). In another study, patients with nonspecific chronic pain selected from a sleep clinic showed serum 25OHD levels <20 ng/mL (McCarty et al 2013). The risk factors for the decrease of vitamin D status in this study were ethnicity, obesity and age.…”
Section: Future Perspectives: Vitamin D Sleep and Painmentioning
confidence: 93%
“…Remarkably, the pathophysiological interactions of CKD-MBD including vit D deficiency and consequent hypocalcemia greatly predispose to MSDs in patients with ESKD [ 1 ]. Similarly, an association has been reported between decreased vitamin D levels and musculoskeletal pain in the general population [ 42 , 43 ]. As well, there has been an association between chronic anemia and musculoskeletal disorders [ 44 ].…”
Section: Discussionmentioning
confidence: 78%
“…Most of these studies have methodological flaws, heterogeneous cohort, smaller sample size and are underpowered to address this issue. However, the majority of the reports from different populations have documented lower vitamin D levels in vague aches and pain than reference populations . Correlation between low back pain in people with modic changes and vitamin D insufficiency also do exist in the literature .…”
Section: Diffuse Aches and Painsmentioning
confidence: 99%